Identification of miR‐93 as a suitable miR for normalizing miRNA in plasma of tuberculosis patients. Issue 7 (8th March 2015) - Barry, Simone E.; Chan, Brian; Ellis, Magda; Yang, YuRong; Plit, Marshall L.; Guan, Guangyu; Wang, Xiaolin; Britton, Warwick J.; Saunders, Bernadette M.
Abstract Tuberculosis (TB) remains a major public health issue. New tests to aid diagnoses and monitor the response to therapy are urgently required. There is growing interest in the use of microRNA (miRNA) profiles as diagnostic, prognostic or predictive markers in a range of clinical and infectious diseases, including Mycobacterium tuberculosis infection, however, challenges exist to accurately normalise miRNA levels in cohorts. This study examined the appropriateness of 12 miRs and RNU6B to normalise circulating plasma miRNA levels in individuals with active TB from 2 different geographical and ethnic regions. Twelve miRs (let‐7, miR‐16, miR‐22, miR‐26, miR‐93, miR‐103, miR‐191, miR‐192, miR‐221, miR‐423, miR‐425 and miR‐451) and RNU6B were selected based on their reported production by lung cells, expression in blood and previous use as a reference miRNA. Expression levels were analysed in the plasma of newly diagnosed TB patients from Australia and China compared with individuals with latent TB infection and healthy volunteers. Analysis with both geNorm and NormFinder software identified miR‐93 as the most suitable reference miR in both cohorts, either when analysed separately or collectively. Interestingly, there were large variations in the expression levels of some miRs, in particular miR‐192 and let‐7, between the two cohorts, independent of disease status. These data identify miR‐93 is a suitable reference miR for normalizing miRNA levels in TB patients, and highlight how environmental, and possibly ethnic, factors influence miRNA expression levels, demonstrating the necessity of assessing the suitability of reference miRs within the study population.